hirst Traps And #Relatable Vines: Investigating A Networked Counterpublic Of Queer Women - Duguay, Stefanie (AoIR Selected Papers of Internet Research, 2017)
This paper examines queer women’s participation and representation on social media through a case study of Vine, Twitter’s now defunct video social network. Launched in 2013, Vine paired a 6.5-second looping video format with social networking features, including follower lists, cross-platform sharing, and hashtagging. Vine’s popularity spiked and plummeted over three years. During this time, queer women’s activity on the platform was visible through their use of LGBT (lesbian, gay, bisexual, trans) hashtags, such as #RainbowGang and #AllQueerHere. This study uses mixed methods to examine queer women’s use of Vine, starting with an in-depth platform analysis followed by textual analysis of 77 videos (“Vines”) by queer women and narrative analysis of interviews with two Viners. Findings indicate that queer women on Vine formed a networked counterpublic while also contributing across identity-related publics until the platform ethos and redesign disrupted these publics. Queer women drew on the affordances of Vine’s looping video to produce intensely affective and narrative videos. They generated affinity through displays of sexual desire in thirst trap videos and relatable stories of shared experiences. They also exchanged narrative performances and humorous skits critiquing normative racial and sexual biases. Sociocultural and technical shifts in the platform led to greater focus on micro-celebrity accounts and design updates included fewer sharing features, leading to queer women’s eventual disengagement from the platform. These findings provide an understanding of queer women’s participation and representation on a visual, mobile platform and illuminate shifting conditions that can foster and stifle networked counterpublics.